Diversity matters – heterogeneity of dopaminergic neurons in the ventral mesencephalon and its relation to Parkinson's Disease. (27th June 2016) - Vogt Weisenhorn, Daniela Maria; Giesert, Florian; Wurst, Wolfgang
Abstract : Several decades of research revealed that the neurons in the ventral mesencephalic dopaminergic complex do not form a homogeneous group in respect to anatomy, physiology, function, molecular identity or vulnerability/dysfunction in diseases like Parkinson's disease (PD). Here, we review how this concept evolved and was refined over time and how it shaped our understanding of the pathogenesis of PD. Source of the midbrain image:www.wikimd.org/wiki/index.php/The_Midbrain_or_Mesencephalon ; downloaded 28.01.2016. See also Figures1 and3 of the paper. This article is part of a special issue on Parkinson disease . Abstract: Dopaminergic neurons in the ventral mesencephalon (the ventral mesencephalic dopaminergic complex) are known for their role in a multitude of behaviors, including cognition, reward, addiction and voluntary movement. Dysfunctions of these neurons are the underlying cause of various neuropsychiatric disorders, such as depression, addiction and schizophrenia. In addition, Parkinson's disease (PD), which is the second most common degenerative disease in developed countries, is characterized by the degeneration of dopaminergic neurons, leading to the core motor symptoms of the disease. However, only a subset of dopaminergic neurons in the ventral mesencephalon is highly vulnerable to the disease process. Indeed, research over several decades revealed that the neurons in the ventral mesencephalic dopaminergic complex do not form a homogeneous group with respect to anatomy, physiology, function, molecular identity or vulnerability/dysfunction in different diseases. Here, we review how the concept of dopaminergic neuron diversity, assisted by the advent and application of new technologies, evolved and was refined over time and how it shaped our understanding of PD pathogenesis. Understanding this diversity of neurons in the ventral mesencephalic dopaminergic complex at all levels is imperative for the development of new and more selective drugs for both PD and various other neuropsychiatric diseases. Several decades of research revealed that the neurons in the ventral mesencephalic dopaminergic complex do not form a homogeneous group in respect to anatomy, physiology, function, molecular identity or vulnerability/dysfunction in diseases like Parkinson's disease (PD). Here, we review how this concept evolved and was refined over time and how it shaped our understanding of the pathogenesis of PD. Source of the midbrain image:www.wikimd.org/wiki/index.php/The_Midbrain_or_Mesencephalon ; downloaded 28.01.2016. See also Figures1 and3 of the paper. This article is part of a special issue on Parkinson disease .